PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT (ERM) TERHADAP NILAI PERUSAHAAN DENGAN DIMEDIASI OLEH KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2019) - Ismah Nur Fajriah; Imam Ghozali (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the effect of Enterprise Risk Management (ERM) disclosure with financial performance as an intervening variable, as well as firm size and managerial ownership as control variable on firm value that is proxied by Tobin’s Q. This research uses a quantitative approach using secondary data from the company’s annual report and financial report. The population of this research is manufacturing companies listed on Indonesia Stock Exchange (IDX) in 2018-2019. The sample determination method used was purposive sampling so that a sample of 230 samples was obtained. The hypothesis in this study was tested using path analysis and Bootstrapping technique. The results showed that ERM has positive direction upon firm value but it is not significant. The results do not support the hypothesis that firms which practice ERM would have higher Tobin’s Q ratio than firms which are not. Financial performance and firm size establish positive and significant relationship with firm value. Meanwhile, the managerial ownership has no significant influence upon the firm value. Other results also showed that financial performance is able to mediate the relationship between ERM and firm value.